The effect of paternal depression and anxiety symptoms on newborn low birth weight - Md Rifin, Sakinah; Md Aris, Mohd Aznan; Nasreen, Hashima E (2018)
Despite significant improvement in health status in Malaysia, the prevalence of low birth weight (LBW) infants is still remained static over the past 12 years1. In past decades, there have been assumptions regarding the potential etiologic association of psychosocial factors with LBW. However, it is widely believed that only mothers are affected by depression and anxiety during pregnancy. Therefore, most studies are focused on mothers. There is no study in Malaysia that shows the impact of paternal depressive and anxiety symptoms on LBW.